Constructing hegemonic masculinities: evidence from Greek narrative performances. (4th February 2015) - Archakis, Argiris; Lampropoulou, Sofia
Abstract : In this article we draw upon the notions of heterosexuality, heteronormativity, agency and responsibility in order to investigate the construction of hegemonic masculinities through stories produced by Greek male adolescents. Our data are part of a broader set of narrative data collected in the context of a research project aiming to record and analyse naturally occurring talk of Greek youths. We adopt the model of narrative positioning in order to explore how young men narratively construct their identities as heterosexual human beings. The narratives at hand deal with sexually related encounters in which our male narrators are involved with women who hold senior, institutional roles. The story topics are presented as unconventional, and our narrators diminish their agency and responsibility for the sexually related acts, which, in turn, are attributed to female characters. We explore and unpack the subtle ways in which our narrators position themselves in relation to heterosexuality and heteronormativity, and how this contributes to the construction of their (hegemonic) masculine selves. To this end, we attempt to probe deeper into the notion of hegemonic masculinity.